Effectiveness of mammogram and ultra-sonogram in the diagnosis of breast cancer in asymptomatic women at Central Karnataka - Byadgi, Sunil S.; Kumar, Vijay; Heggeri, Pramod; Patil, Nagaraj V.; Yerriswamy, Parvathareddy; Jayasimha, V. L.; Somashekar, Nishanth; C. S., Vinodkumar (International Surgery Journal, 2022)
Background: Breast cancer is one of the most common cancers among women around the world. Some occult breast cancers can be missed when using ultrasound or mammogram alone. Considering this background, the study was performed to highlight the improved diagnostic efficacy of identifying breast cancer when using both ultrasound and mammogram as a combined modality. Methods: A total of 150 cases of suspected breast cancer were studied over a period of 2 years. Ultrasonography, and mammography were done by two independent radiologists and the results were analyzed. The patients were tested for BRCA1/2 gene mutations. Histopathology was done finally to confirm the diagnoses. Results: The 39 cases out of 150 asymptomatic women screened for breast cancer showed that they were positive for breast cancer by histopathology and 38 were positive by mammogram and ultra-sonogram. Cancer was prominently diagnosed in the age group of more than 40 years (92.3%) and 82.1% of women were in premenopausal stage. High BMI had a statistically significant correlation with breast cancer. The 71.7% of breast cancer cases were obese and 25.6% were overweight individuals. 89.7% of breast cancer cases were from the urban population. Detection of mutation in the BRCA gene showed 28 cases with a mutation in the BRCA-1 gene and 4 cases with a mutation in the BRCA-2 gene. Conclusions: The study confirms that mammography in addition to ultrasonography improves the sensitivity of detection of occult breast cancer in asymptomatic women.